China and the challenge of economic globalization the impact of WTO membership - Fung, Hung-gay; Pei, Changhong; Zhang, Kevin H. (Gale virtual reference library, 2006)
"Evaluates the implications of China's WTO membership on the nation and provides policy guidance for those doing business in China or working with the Chinese economy."--GVRL description.